Elasticidad de la demanda por medicamentos en el mercado farmacéutico privado en Colombia (2012)
This investigation estimated the elasticity of the intramolecular demand between generics and brand name in pharmaceutical private market in Colombia for three pathologies: Essential Hypertension, Diabetes and hyperlipidemia, from dynamic specification of the AIDS model based on cointegration techniques. The intramolecular price elasticity estimated shows that both generic and brand name drug are inelastic and does not respond to price changes, they are luxury goods from expenditure elasticity results and seems to exist intramolecular substitutability because of the coefficient sign in cross-price elasticity.